Mass spectrometry-based metabolomics uncovers distinct metabolic signatures and potential therapeutic targets in Plasmodium knowlesi - Naphatsamon Uthailak; Sadudee Chotirat; Ammarind Anatjitsupha; Waraporn Thongyod; Phornpimon Tipthara; Jetsumon Sattabongkot; Joel Tarning; Wang Nguitragool; Onrapak Reamtong (PLoS ONE, 2025)
Malaria remains a major global health challenge, caused by several Plasmodium species and transmitted via mosquito vectors. Among these, Plasmodium knowlesi is notable for its zoonotic nature, capable of infecting both macaques and humans. The incidence of P. knowlesi infections has been rising, particularly in Southeast Asia, raising public health concerns. However, compared to other Plasmodium species, the biology, pathophysiology, and transmission dynamics of P. knowlesi remain poorly understood. Given the absence of a licensed vaccine and the increasing threat of drug resistance, a deeper understanding of P. knowlesi biology is essential for effective control and management strategies. This study investigates the metabolomic landscape of P. knowlesi across three intraerythrocytic stagesring, trophozoite, and schizont using mass spectrometry-based metabolomics to gain insights into parasite biology. The analysis revealed distinct metabolic profiles, particularly in the ring stage compared to the other two stages. While glycerophospholipid metabolism and sphingolipid de novo biosynthesis emerged as key pathways associated with common metabolites across all stages, phosphatidylserine synthesis was specifically linked to ring-stage-biased metabolites. Notably, CDP-diacylglycerol-inositol 3-phosphatidyltransferase was highlighted as a promising target based on shared and stage-biased metabolites. Collectively, our findings offer a comprehensive metabolomic profile of P. knowlesi blood-stage development, enhancing our understanding of its biology and identifying potential drug targets that could support the development of novel therapeutic strategies against P. knowlesi malaria.